Satisfaction with the implementation of developmental tasks in the course of life and the sense of well-being in late adulthood - Liberska, Hanna (Magyar Gerontológia, 2021)
Introduction The subject of the sense of psychological well-being in people in late adulthood and its determinants has been of great interest for several dozen years among researchers and broad social groups, including people of senior age. Aims The aim of the presented research was to explain the relationship between coping with life challenges, which are developmental tasks culturally assigned to successive periods of adult life, and the sense of well-being in the last period of life. The study also drew attention to the importance of selected socio-demographic variables for the sense of well-being of people in late adulthood, namely gender, age, level of education, family situation and material (financial) condition. In line with the positive psychology approach, these factors were expected to be of limited importance for the sense of well-being. Methodology 155 people aged over 65 (late adulthood) took part in the study, 53% of whom were men and 47% of women. The author’s questionnaire was used to examine satisfaction with the implementation of developmental tasks (Liberska, 2019), the Mental Wellbeing Questionnaire (L.Wojciechowska, 2008) and a questionnaire collecting basic sociodemographic data. The analysis of the research results showed significant relationships between the implementation of developmental tasks and the sense of well-being. Age of the respondents did not differentiate the sense of well-being. Conclusion People’s sense of well-being in late adulthood is related to coping with developmental tasks in adult life and the current family and economic situation. 1. the results of the statistical analysis did not show statistically significant differences between men and women in the level of psychological well-being: t (152) = -0,63, p = 0,52 (women – M = 87,25, SD = 12,73; men – M = 88,52, SD = 12). 2. people with higher education had a higher level of the general indicator of the sense of well-being than people with secondary (Z=-2.04, p=0.041), vocational (Z=-3.52, p=0.001) and primary education (Z=-3.22, p=0.01) 3. financial status differentiates the sense of well-being of people in late adulthood: people with good economic status have a higher sense of well-being than people with average status (Z = -3.23, p = 0.001) and below average (Z = -2.03; p = 0.043) 4. the results of the statistical analysis showed that people with different marital status differ in the level of mental well-being: married people in late adulthood have a significantly higher level of mental well-being than widowed people (Z=-3.18, p=0.001). 5. among the six dimensions that create mental well-being, the highest value was obtained on the self-acceptance subscale; ANOVA shows significant differences between the subscales of the sense of well-being; F= 7829,05; p< 0,001; η2=0,99). Generally, this result confirms the importance of self-acceptance for the general psychosocial condition of a person (see Ryff, 1989). References: Liberska, H. (2019). Żródła satysfakcji z życia w starości. W: M.Kielar-Turska (red.), Siła umysłu w starości. Starość: jak ją widzi psychologia (s. 537-552). Kraków: Akademia Ignatianum. Ryff, C. D. (1989). Happiness Is Everything or Is It? Explorations on the Meaning of Psychological Wellbeing. Journal of Personality and Social Psychology, 57, 1069-1081; http://dx.doi.org/10.1037/0022-3514.57.6.1069 Wojciechowska, L. (2008). Style starzenia się a subiektywny dobrostan kobiet w późnej dorosłości, studiujących na uniwersytecie trzeciego wieku. Polskie Forum Psychologiczne, 2, 106- 123.